2015
DOI: 10.1177/0301006615594264
|View full text |Cite
|
Sign up to set email alerts
|

Stereo-Curvature Aftereffect Is Due to More Than Shape Curvature Adaptation

Abstract: For stereo-curvature aftereffect (sCAE), there is no agreement on whether adaptation occurs at the disparity-specified stage, the percept-specified stage, or both. Additionally, it remains uncertain whether retinal-position-dependent sCAE can be induced by possible adaptation to disparity-specified sources. Our study aimed to investigate the dependency and processing levels of adaptation underlying sCAE using dynamic spherical adaptation stimuli with static fixation. Experiment I examined the dependency by dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…These researchers concluded that the disparity per se, not the perceived depth, was adapted by the visual system. Yan and Shigemasu (2015) dynamically changed the location, size, and depth of spherical adaptation stimuli and found that both disparity- and percept-specified processes were involved in stereo-curvature adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…These researchers concluded that the disparity per se, not the perceived depth, was adapted by the visual system. Yan and Shigemasu (2015) dynamically changed the location, size, and depth of spherical adaptation stimuli and found that both disparity- and percept-specified processes were involved in stereo-curvature adaptation.…”
Section: Introductionmentioning
confidence: 99%